MODERN HISTORY OF KAZAKHSTAN - Bekmagambetova, M. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The course of lectures is devoted to the most important period of domestic history. The process of formation of socio-economic, political and spiritual bases of modern Kazakhstan is considered. It is designed for students, undergraduates, all interested in the history of the Republic of Kazakhstan.